Oxygen stable isotopes in the nuclear fuel cycle: Assessment of the potential for determining the fabrication and provenance history of anhydrous and hydrous uranium oxides - Erik J.H. Oerter; Miguel Cisneros; Eric Pili; Michael Singleton; Pierre Agrinier; Travis Tenner; Ruth Kips (Applied Geochemistry, 2026)

Triple oxygen and hydrogen stable isotope composition of water in Murchison carbonaceous chondrite accessed by thermogravimetry-enabled laser spectroscopy - Erik J. Oerter; Alexandre Garenne; Miguel Cisneros; George D. Cody; Michael Singleton; Conel M. O’D. Alexander (Chemical Geology, 2025)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genome-Wide Association Analysis of the Sense of Smell in U.S. Older Adults: Identification of Novel Risk Loci in African-Americans and European-Americans - Jing Dong; Annah Wyss; Jingyun Yang; T. Ryan Price; Aude Nicolas; Michael Nalls; Greg Tranah; Nora Franceschini; Zongli Xu; Claudia Schulte; Alvaro Alonso; Steven R. Cummings; et al. (Molecular Neurobiology, 2017)

Reconstructing the demographic history of orang‐utans using Approximate B ayesian Computation - Alexander Nater; Maja P. Greminger; Natasha Arora; Carel P. van Schaik; Benoit Goossens; Ian Singleton; Ernst J. Verschoor; Kristin S. Warren; Michael Krützen (Molecular Ecology, 2015)
Investigating how different evolutionary forces have shaped patterns of DNA variation within and among species requires detailed knowledge of their demographic history. O rang‐utans, whose distribution is currently restricted to the S outh‐ E ast A sian islands of B orneo ( P ongo pygmaeus ) and S umatra ( P ongo abelii ), have likely experienced a complex demographic history, influenced by recurrent changes in climate and sea levels, volcanic activities and anthropogenic pressures. Using the most extensive sample set of wild orang‐utans to date, we employed an Approximate B ayesian Computation ( ABC ) approach to test the fit of 12 different demographic scenarios to the observed patterns of variation in autosomal, X ‐chromosomal, mitochondrial and Y ‐chromosomal markers. In the best‐fitting model, Sumatran orang‐utans exhibit a deep split of populations north and south of L ake T oba, probably caused by multiple eruptions of the T oba volcano. In addition, we found signals for a strong decline in all S umatran populations ~24 ka, probably associated with hunting by human colonizers. In contrast, B ornean orang‐utans experienced a severe bottleneck ~135 ka, followed by a population expansion and substructuring starting ~82 ka, which we link to an expansion from a glacial refugium. We showed that orang‐utans went through drastic changes in population size and connectedness, caused by recurrent contraction and expansion of rainforest habitat during Pleistocene glaciations and probably hunting by early humans. Our findings emphasize the fact that important aspects of the evolutionary past of species with complex demographic histories might remain obscured when applying overly simplified models.

Mouse divalent metal transporter 1 is a copper transporter in HEK293 cells - Miguel Arredondo; María José Mendiburo; Sebastián Flores; Steven T. Singleton; Michael D. Garrick (BioMetals, 2014)

Hyperfine interactions and electron distribution in FeIIFeI and FeIFeI models for the active site of the [FeFe] hydrogenases: Mössbauer spectroscopy studies of low-spin FeI - Sebastian A. Stoian; Chung-Hung Hsieh; Michael L. Singleton; Andrea F. Casuras; Marcetta Y. Darensbourg; Kelsey McNeely; Kurt Sweely; Codrina V. Popescu (JBIC Journal of Biological Inorganic Chemistry, 2013)

Submarine Groundwater Discharge-Derived Nutrient Loads to San Francisco Bay: Implications to Future Ecosystem Changes - Kimberly A. Null; Natasha T. Dimova; Karen L. Knee; Bradley K. Esser; Peter W. Swarzenski; Michael J. Singleton; Mark Stacey; Adina Paytan (Estuaries and Coasts, 2012)

Long-term simulation of in situ biostimulation of polycyclic aromatic hydrocarbon-contaminated soil - Stephen D. Richardson; Maiysha D. Jones; David R. Singleton; Michael D. Aitken (Biodegradation, 2012)

Pyrosequence analysis of bacterial communities in aerobic bioreactors treating polycyclic aromatic hydrocarbon-contaminated soil - David R. Singleton; Stephen D. Richardson; Michael D. Aitken (Biodegradation, 2011)

Stable‐isotope probing of the polycyclic aromatic hydrocarbon‐degrading bacterial guild in a contaminated soil - Maiysha D. Jones; Douglas W. Crandell; David R. Singleton; Michael D. Aitken (Environmental Microbiology, 2011)
Summary The bacteria responsible for the degradation of naphthalene, phenanthrene, pyrene, fluoranthene or benz[ a ]anthracene in a polycyclic aromatic hydrocarbon (PAH)‐contaminated soil were investigated by DNA‐based stable‐isotope probing (SIP). Clone libraries of 16S rRNA genes were generated from the 13 C‐enriched (‘heavy’) DNA recovered from each SIP experiment, and quantitative PCR primers targeting the 16S rRNA gene were developed to measure the abundances of many of the SIP‐identified sequences. Clone libraries from the SIP experiments with naphthalene, phenanthrene and fluoranthene primarily contained sequences related to bacteria previously associated with the degradation of those compounds. However, Pigmentiphaga ‐related sequences were newly associated with naphthalene and phenanthrene degradation, and sequences from a group of uncultivated γ‐ Proteobacteria known as Pyrene Group 2 were newly associated with fluoranthene and benz[ a ]anthracene degradation. Pyrene Group 2‐related sequences were the only sequences recovered from the clone library generated from SIP with pyrene, and they were 82% of the sequences recovered from the clone library generated from SIP with benz[ a ]anthracene. In time‐course experiments with each substrate in unlabelled form, the abundance of each of the measured groups increased in response to the corresponding substrate. These results provide a comprehensive description of the microbial ecology of a PAH‐contaminated soil as it relates to the biodegradation of PAHs from two to four rings, and they underscore that bacteria in Pyrene Group 2 are well‐suited for the degradation of four‐ring PAHs.

Relations of hydrogeologic factors, groundwater reduction-oxidation conditions, and temporal and spatial distributions of nitrate, Central-Eastside San Joaquin Valley, California, USA - Matthew K. Landon; Christopher T. Green; Kenneth Belitz; Michael J. Singleton; Bradley K. Esser (Hydrogeology Journal, 2011)

Effects of enrichment with phthalate on polycyclic aromatic hydrocarbon biodegradation in contaminated soil - David R. Singleton; Stephen D. Richardson; Michael D. Aitken (Biodegradation, 2008)

Identification and quantification of uncultivated Proteobacteria associated with pyrene degradation in a bioreactor treating PAH‐contaminated soil - David R. Singleton; Ramiah Sangaiah; Avram Gold; Louise M. Ball; Michael D. Aitken (Environmental Microbiology, 2006)
Summary Uncultivated bacteria associated with the degradation of pyrene in a bioreactor treating soil contaminated with polycyclic aromatic hydrocarbons (PAH) were identified by DNA‐based stable‐isotope probing (SIP) and quantified by real‐time quantitative PCR. Most of the 16S rRNA gene sequences recovered from 13 C‐enriched DNA fractions clustered phylogenetically within three separate groups of β‐ and γ‐Proteobacteria unassociated with described genera and were designated ‘Pyrene Groups 1, 2 and 3’. One recovered sequence was associated with the Sphingomonas genus. Pyrene Groups 1 and 3 were present in very low numbers in the bioreactor but represented 75% and 7%, respectively, of the sequences recovered from 16S rRNA gene clone libraries constructed from 13 C‐enriched DNA. In a parallel time‐course incubation with unlabelled pyrene, there was between a 2‐ and 4‐order‐of‐magnitude increase in the abundance of 16S rRNA genes from Pyrene groups 1 and 3 and from targeted Sphingomonas spp. over a 10 day incubation. Sequences from Pyrene Group 2 were 11% of the SIP clone libraries but accounted for 14% of the total bacterial 16S rRNA genes in the bioreactor community. However, the abundance of this group did not increase significantly in response to pyrene disappearance. These data indicate that the primary pyrene degraders in the bioreactor were uncultivated, low‐abundance β‐ and γ‐Proteobacteria not previously associated with pyrene degradation.

DMT1: A mammalian transporter for multiple metals - Michael D. Garrick; Kevin G. Dolan; Craig Horbinski; Andrew J. Ghio; Dennis Higgins; Michael Porubcin; Elizabeth G. Moore; Lucille N. Hainsworth; Jay N. Umbreit; Marcel E. Conrad; Lee Feng; Agnieska Lis; et al. (BioMetals, 2003)